Association of classical symptomatology with actual thyroid disease and the assessment of variations observed in thyroid profile: a comparative study between the elderly and the young adults - Abraham, Lissa; Varghese, Sajit (International Journal of Advances in Medicine, 2020)
Background: The classical symptoms of thyroid dysfunction are valuable in being related to the value of TSH (thyroid stimulating hormone) and the occurrence of actual thyroid disease. There are significant variations seen in the clinical presentation of thyroid disorder in elderly patients, when compared to young adults, and the biochemical parameters of thyroid function also vary according to age and gender. Authors aimed to study the association of classical symptomatology of thyroid dysfunction with the presence of actual biochemically proven thyroid disorder, separately in two groups: one comprising elderly patients (≥60 years)-Group A and other comprising young adult patients (25-50 years)-Group B. Methods: Patients attending the General Medicine out-patient department at Pushpagiri Medical College Hospital, Tiruvalla, Kerala, from December 2019 to January 2020 having any of the classical symptomatology as described in the inclusion criteria, were enrolled. Clinical assessment and data collection was followed by statistical analysis after sorting out the patients into two groups. Results: In Group A, the symptoms which turned out non-significant for biochemical thyroid disease were chronic constipation, menorrhagia, pedal edema and pallor. In Group B, the picture was somewhat similar, but importantly, chronic constipation turned out to be significant for hypothyroidism while menorrhagia, pedal edema and pallor were insignificant with actual disease. Overt hypothyroidism was the most common thyroid disorder detected in both the groups. Conclusions: appreciating the variability and importance of clinical symptoms of thyroid disorders helps in correctly diagnosing them, especially in the vulnerable elderly population.